IDE UNTUK MENYUSUN PROPOSAL PENELITIAN SENI TARI - R.M. Pramutomo (Institut Seni Indonesia Surakarta, 2000)
Dance studies have been establishing by inspecting its abilities to some new perspectives in the research’s field. Indeed, research isa confusing term as Henstein said. The previous curiousities has been inspected by Henstein in orderto arrange a research proposal. Based on a term a research is scholarly, through this article I am going to examine a basic element of previous curiousities called systematic of inquiry By inspecting systematic of inquiry, it will be supporting a new perspective in the research proposal as welL This article is also going to strive the difficulies of finding idea, and hopefully helping to understand precisely what we mean when we speak about research in a scholarly sense.Keywords: idea of research, research’s scholarly, research proposal.